Perlindungan Hak Kebebasan Berpendapat Di Media Sosial Bagi Pegawai Negeri Sipil Dalam Perspektif Hak Asasi Manusia (Analisis Putusan Nomor. 3168/Pid.Sus/2018/PN MDN, Putusan Nomor 806/Pid.Sus/2019/PT MDN, Dan Putusan Mahkamah Agung Nomor 3880/TU/2020/2667 K/PID.SUS/2020) - Syafrizal Syafrizal; Budiman Ginting; Mirza Nasution; Jelly Leviza (Iuris Studia: Jurnal Kajian Hukum, 2022)
The phenomenon of hate speech and hoaxes with the nuances of hate speech is increasingly happening through social media. many civil servants are entangled in legal cases related to hate speech in their reactions on social media. So this research is intended to analyze how the form of legal protection for freedom of expression on social media for civil servants is regulated in international human rights instruments and laws and regulations in Indonesia. The results of this study indicate that the legal protection of the right to freedom of expression for civil servants on social media is a human right that has been regulated and guaranteed in national legal instruments and is implicitly regulated in international human rights legal instruments. The legal protection regulated in the ITE Law is to continue to guarantee the implementation of the freedom for civil servants to express opinions on social media as long as it is not classified as hate speech, namely insults, defamation, blasphemy, provoking, inciting, fake news that has the impact of violence, social conflict, and discrimination. to provide clear boundaries that an action can be classified as hate speech, there are 6 (six) parameters: 1. Malicious intent, 2. Must be informative, 3. There is a clear/specific target of hatred, 4. Context of hate speech. must be precise, 5. The scope of hate speech, and 6. There is a quick reaction of hatred